A new strategy formulation model: the strategic initiative model: Strateji yaratımı için yeni bir model: stratejik insiyatif modeli - Başkan, Burçak (My University, 1997)
unknown
Keywords: STRATEJİ; STRATEJİK YÖNETİM-İŞLETMELER